2022
DOI: 10.1002/tox.23458
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate aggravates CCl4‐induced hepatic fibrosis via HMGB1/TLR4/Smad signaling

Abstract: Perfluorooctane sulfonate (PFOS) is a widespread environmental pollutant and may cause a variety of adverse health effects. The hepatotoxicity of PFOS has attracted particular attention, given the fact that the liver has one of the highest PFOS accumulations among human tissues. In this study, we revealed that subchronic PFOS exposure may exacerbate carbon tetrachloride (CCl 4 )-induced liver fibrosis in animal models. Administration with 1 mg/kg PFOS every other day for 56 days dramatically enhanced CCl 4 -me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…It may be related to changes in lipid and bile acid metabolism ( 9 , 59 ). In animal models, exposure to subchronic PFOS has been found to enhance hepatic stellate cell (HSC) activation and exacerbate carbon tetrachloride (CCl 4 )-induced liver fibrosis ( 60 ), consistent with the outcomes of Sen’s study, which showed that PFOS was positively associated with hepatic fibrosis in adults ( 9 ). In contrast, a study including adults from the C8 Health Project in the USA showed that cumulative PFOA exposure had no effect on all liver diseases, enlarged liver, or cirrhosis ( 58 ).…”
Section: Relationship Between Nafld and Edcssupporting
confidence: 60%
“…It may be related to changes in lipid and bile acid metabolism ( 9 , 59 ). In animal models, exposure to subchronic PFOS has been found to enhance hepatic stellate cell (HSC) activation and exacerbate carbon tetrachloride (CCl 4 )-induced liver fibrosis ( 60 ), consistent with the outcomes of Sen’s study, which showed that PFOS was positively associated with hepatic fibrosis in adults ( 9 ). In contrast, a study including adults from the C8 Health Project in the USA showed that cumulative PFOA exposure had no effect on all liver diseases, enlarged liver, or cirrhosis ( 58 ).…”
Section: Relationship Between Nafld and Edcssupporting
confidence: 60%
“…Organisms can be exposed to PFOS through ingestion of food and drinking water, breathing air, and exposure to contaminated medium 2 . The use of PFOS has been restricted due to its environmental persistence and biotoxicity 3 . Unfortunately, PFOS is now widely detected in the environment, and continually poses a great threat to the health of organisms 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of PFOS has been restricted due to its environmental persistence and biotoxicity. 3 Unfortunately, PFOS is now widely detected in the environment, and continually poses a great threat to the health of organisms. 4 Existing reports have shown that immunosuppression have been observed in the general population exposed to PFOS.…”
mentioning
confidence: 99%
“…Its inactivation could reduce liver inflammation, stellate cell activation and collagen deposition. Ctsb deficiency could down‐regulate the expression of tumor necrosis factor‐α (TNF‐α) and transcription inhibitor actinomycin d, induce mitochondria to release cytochrome c and caspase activation, thereby promoting hepatocyte apoptosis 47–50 . However, most of these observations come from hepatocytes and hepatic stellate cells cultured in vitro.…”
Section: Discussionmentioning
confidence: 99%